La motivación y el perfil del docente - Tigmasa Chusin, Jhinson Fernando (2018)
The present work research is carried out with the purpose of exposing the fundamental considerations that implies the motivation and the teacher profile in the learning process and the impact that they generate in the academic performance of the students empowering them to fulfill with its pedagogical activities in a stimulating environment and thus substantially improve the environment in which learners interact daily; The motivation will be one of the main pillars with which the teacher must act since a motivated student will always be able to develop to the maximum their skills and skills being thus a reference of leadership for others, therefore the teacher must work based on objective and solid planning that allows students to interact efficiently reaching goals and leaving a legacy of work delivering and empowering their arduous educational work; In fact the purpose of this project is focused on the purpose of having a tool that allows to denote that the motivating teacher is the one who entrenches through various strategies an educational climate of confidence in order to give due continuity to the Formative process and thus fulfilling the institutional guidelines established providing a quality education and warmth.